Scope of Personalized Homeopathy in Psoriasis: A Treatment Series of Four Cases (Bioresearch Communications, 2026)
Background: Psoriasis is a common, chronic autoimmune-genetic disorder of the skin, often elicited by psychological stressors and environmental factors. The plaque variant is most frequently encountered, with guttate, pustular, inverse, and erythrodermic types also reported. Disease severity is typically quantified using modalities such as the Psoriasis Area and Severity Index (PASI). Conventional treatments—including topical agents, phototherapy, and systemic medications—are available, though many patients report limited satisfaction due to side effects, incomplete responses, and cost burdens. This case series investigates the therapeutic outcomes of individualized homeopathic medicine in patients diagnosed with plaque psoriasis in Bangladesh. Methods: Four adult patients with clinically confirmed plaque psoriasis received personalized homeopathic remedies selected on symptoms similarity, namely Calcarea carbonica, Lycopodium clavatum, Natrum muriaticum and Sepia. Treatment protocols included detailed documentation of remedy selection criteria, preparation methods, dosing regimens, and follow-up schedules. Baseline and follow-up assessments were conducted using PASI scoring, photographic documentation of lesions, and patient-reported satisfaction scores. Results: All patients demonstrated a measurable decrease in PASI scores over the treatment period. Clinical photographs reflected visible regression of plaques, while subjective satisfaction ratings improved consistently across cases. No significant adverse effects were recorded. Conclusions: In this series of four cases, individualized homeopathic treatment appeared to yield positive clinical outcomes in plaque psoriasis, as evidenced by both objective and subjective measures. Although limited by small sample size and absence of a control group, these findings suggest a potential role for homeopathic therapies in psoriasis management. Further research involving larger cohorts and controlled study designs is reasonable to validate these preliminary observations.Bioresearch Commu. 12(1): 2078-2085, 2026 (January)